2020
DOI: 10.3390/s20174797
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Activity Trackers in the Management of Rheumatic Diseases: Where Are We in 2020?

Abstract: In healthcare, physical activity can be monitored in two ways: self-monitoring by the patient himself or external monitoring by health professionals. Regarding self-monitoring, wearable activity trackers allow automated passive data collection that educate and motivate patients. Wearing an activity tracker can improve walking time by around 1500 steps per day. However, there are concerns about measurement accuracy (e.g., lack of a common validation protocol or measurement discrepancies between different device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 105 publications
(145 reference statements)
0
14
0
3
Order By: Relevance
“…In recent years, an ongoing evolution in technology and digitalisation has resulted in an ever-increasing number of mHealth-applications [ 8 ]. In addition, wearable activity trackers (WATs) are emerging as a promising tool to monitor biometric data [ 9 ]. When routinely integrated into health care and linked to electronic medical patient files, these mHealth-applications and WATs could prove to be an added value in (tele)monitoring treatment adherence, adverse treatment effects or symptoms and disease activity in RA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an ongoing evolution in technology and digitalisation has resulted in an ever-increasing number of mHealth-applications [ 8 ]. In addition, wearable activity trackers (WATs) are emerging as a promising tool to monitor biometric data [ 9 ]. When routinely integrated into health care and linked to electronic medical patient files, these mHealth-applications and WATs could prove to be an added value in (tele)monitoring treatment adherence, adverse treatment effects or symptoms and disease activity in RA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mehrere kĂŒrzlich erschienene Studien erachten Wearables als ein potentiell sinnvolles Messinstrument, um bei rheumatologischen Patienten die körperliche AktivitĂ€t zu messen 54 , aber auch den Patienten zu motivieren 55 . Auch in Kombination mit einem Physiotherapeuten kann die Nutzung eines Bewegungsmessers eine potentiell sinnvolle Intervention zur Schmerzreduktion und verbesserter Bewegungsgewohnheit darstellen 24 .…”
Section: Arten Von Hilfsmittelnunclassified
“…Die Standardisierung der Datenanalyse und -Interpretation ist massiv erschwert. Zudem sind regelmĂ€ĂŸige QualitĂ€tskontrollen notwendig, um die eHealth-Produkte zuverlĂ€ssig und korrekt auf dem medizinischen Markt einsetzten zu können 54 55 58 . O’Brien et al (2020) konnten beispielsweise die ValiditĂ€t des Wearables activPAL3 ÎŒ ℱ zur Messung von sitzender TĂ€tigkeit und körperlicher AktivitĂ€t prĂŒfen und entwickelten RA-spezifische Cut-Offs zur Quantifizierung der IntensitĂ€t der AktivitĂ€t 59 .…”
Section: Arten Von Hilfsmittelnunclassified
See 1 more Smart Citation
“…Patients also appreciate the ability to a more personalized care by selecting the outcomes that are most important to them, change and adapt their symptom monitoring as their disease progresses and their treatments change ( 22 ). Further, it is reported that regular monitoring of RA patients to detect disease flares improves outcomes, and a pilot study applying machine learning to activity tracker steps showed that physical activity was strongly linked to disease flares and that patterns of physical activity could be used to predict flares with great accuracy, with a sensitivity and specificity above 95% ( 23 ). In addition, patients and caregivers express a high level of satisfaction with the use of telemedicine without any complaints of loss of information compared to traditional consultations ( 24 ).…”
Section: Advantages and Limitations For Telemedicine In Rheumatologymentioning
confidence: 99%